The Effect of ASN Motivation and Social Capital on Collaboration in the Implementation of One Data Indonesia in Ogan Komering Ilir Regency - Adi, Yuanita Permata; Alfatih, Andy; Alamsyah, Alamsyah (ARISTO, 2026)
This study aims to determine the influence of motivation and social capital of civil servants (ASN) on Collaboration in the implementation of the One Data policy in Ogan Komering Ilir Regency. The research employs a descriptive quantitative approach, emphasizing numerical data analysis using multiple linear regression methods. The study population consists of 78 civil servants involved in the implementation of the One Data Indonesia policy in Ogan Komering Ilir Regency, making the sample a saturated sample or census. Questionnaires were collected using instruments based on a Likert scale. The study concludes that both motivation and social capital of civil servants have a significant impact on Collaboration in implementing One Data Indonesia in Ogan Komering Ilir Regency. Social capital has a greater influence than motivation, indicating that strengthening trust, social networks, and cooperative relationships should be the primary focus to enhance the quality of collaboration among civil servants and ensure the success of public policies.